2014
DOI: 10.1007/s12031-014-0251-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ceftriaxone on Chronic Ethanol Consumption: a Potential Role for xCT and GLT1 Modulation of Glutamate Levels in Male P Rats

Abstract: Alterations in glutamatergic neurotransmission have been suggested to affect many aspects of neuroplasticity associated with alcohol/drug addiction. We have previously shown that ceftriaxone, a β-lactam antibiotic known to upregulate glutamate transporter 1 (GLT1), reduced ethanol intake after five weeks of free-choice ethanol drinking paradigm in male alcohol-preferring (P) rats. Evidence suggests that differential effects involving alterations of glutamatergic neurotransmission occur after long term ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 53 publications
7
38
0
Order By: Relevance
“…It remains to be examined if the change in extracellular glutamate after ethanol exposure is mediated primarily by the downregulation of GLT-1 protein or the impaired transport function of GLT-1. Regardless, CEF treatment normalized GLT-1 protein levels in NAc and is consistent with earlier reports showing GLT-1 upregulation in NAc by CEF (Rothstein et al, 2005, Sari et al, 2010, Sari et al, 2011, Qrunfleh et al, 2013, Sari et al, 2013a, Sari et al, 2013b, Abulseoud et al, 2014, Rao and Sari, 2014). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It remains to be examined if the change in extracellular glutamate after ethanol exposure is mediated primarily by the downregulation of GLT-1 protein or the impaired transport function of GLT-1. Regardless, CEF treatment normalized GLT-1 protein levels in NAc and is consistent with earlier reports showing GLT-1 upregulation in NAc by CEF (Rothstein et al, 2005, Sari et al, 2010, Sari et al, 2011, Qrunfleh et al, 2013, Sari et al, 2013a, Sari et al, 2013b, Abulseoud et al, 2014, Rao and Sari, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, CEF is known to have neuroprotective effects (Mimura et al, 2011) and attenuated cocaine-seeking (Sari et al, 2009, Knackstedt et al, 2010, Sondheimer and Knackstedt, 2011), cannabinoid tolerance (Gunduz et al, 2011), amphetamine-induced hyperactivity and behavioral sensitization (Rasmussen et al, 2011a), and morphine-evoked hyperthermia (Rawls et al, 2007). CEF has also been reported to attenuate both chronic and relapse-like ethanol drinking (Sari et al, 2011, Qrunfleh et al, 2013, Sari et al, 2013a, Sari et al, 2013b, Alhaddad et al, 2014, Rao and Sari, 2014), and ethanol-withdrawal manifestations (Abulseoud et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we have recently reported that chronic ethanol consumption was associated with significant downregulation of xCT levels in the NAc and PFC in P rats (Alhaddad et al 2014a). Ceftriaxone is known to upregulate xCT expressions and was found effective in abolishing drug-seeking behavior (Knackstedt et al 2010; Lewerenz et al 2009; Rao and Sari 2014a; Trantham-Davidson et al 2012). Given the possible role of xCT in the development of addiction, we have revealed in this study the ability of ceftriaxone to upregulate xCT expressions in the NAc and PFC of ethanol-dependent P rats compared to saline-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone, a β-lactam antibiotic, is a known modulator of the major glutamate transporters, glutamate transporter 1 (GLT1) and cystine/glutamate antiporter, xCT (system x c − ) (Knackstedt et al 2010; Lewerenz et al 2009; Rao and Sari 2014a; Rothstein et al 2005). Ceftriaxone treatment has proven to be effective in several drug abuse animal models (Abulseoud et al 2012; Alajaji et al 2013; Rasmussen et al 2011; Sari et al 2013a; Sari et al 2011; Sondheimer and Knackstedt 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[27]]. Several studies from our laboratory reported that the increases in xCT and GLT-1 expressions are linked to the attenuation of ethanol consumption in male P rats [14, 17, 18]. In addition, chronic consumption of ethanol can lead to downregulation of xCT expression in the NAc and PFC [13].…”
Section: Discussionmentioning
confidence: 99%